The influence of ameliorant, nutrient solution and biofertilizer on soil p, plant p uptake, and yield of red chili - Wong, Mui Yun; Fitriatin, Betty Natalie; Dupa, Putri Siska Ekayanti; Fauziah, Nicky Oktav; Simarmata, Tualar (Universitas Islam Negeri, Sunan Gunung Djati, Bandung, 2024)
The productivity and quality of red chili are greatly influenced by soil conditions and the availability of nutrients. Nutrients play a critical role in the growth and development of red chili plants. This experiment aimed to determine the combination of ameliorant, nutrient solution, and biofertilizer on the population of phosphate-solubilizing bacteria (PSB), available P, P-uptake, and red chili production in Inceptisols. The experiment was conducted at the experimental field of the Faculty of Agriculture, Universitas Padjadjaran. The experiment used a Randomized Complete Block Design (RCBD) with seven treatments and four replications, consisting of control, NPK, and nutrient solution (NS) with doses of 0, 6, and 12 kg ha-1 biofertilizers. The dosage used in a single application was 15 g plant-1 of NPK fertilizer and 300 mL plant-1 of nutrient solution. The base fertilizer consisted of manure in the control treatment and an ameliorant in other treatments at a dose of 4 t ha-1. The results showed that the combination of ameliorant + NPK + 6 kg ha-1 biofertilizer increased PSB population (4.93 x 106 CFU mL-1), available P (15.4 ppm), and P-uptake (0.74 g plant-1). Meanwhile, the combination of ameliorant + nutrient solution + 6 kg ha-1 biofertilizer increased fruit diameter (15 mm), and length of red chili (17.3 cm). Correlation analysis indicated positive correlation between red chili production with stem diameter and fruit length, but a negative correlation with P-uptake. Regression analysis indicated that stem diameter and PSB population had the most dominant effect on red chili yield.